MERGER ANTARA XL AXIATA DENGAN AXIS TELECOM INDONESIA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Santika Subawa, Agus Gede; Mas Aryani, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
This paper is titled Merger Between XL With Axis Telecom Indonesia in thePerspective of Law Number 5 Year 1999 concerning the Prohibition of MonopolisticPractices and Unfair Business Competition. This paper aims to determine whatcriteria are prohibited mergers in the competition and whether the merger XL andAxis Telecom Indonesia, including mergers are prohibited in terms of Law Number 5Year 1999 In writing this paper uses normative legal research, legal researchliterature. Mergers are prohibited in competition is that the merger may lead tomonopolistic practices and unfair business competition. XL Axiata merger with AxisTelecom Indonesia indicated violation of the provisions of Article 28 and 17 of LawNumber 5 of 1999, and in violation of Article 25 (1) of Government RegulationNumber 53 Year 2010 on the Use of Radio Frequency Spectrum and Satellite Orbit.
Keywords: Mergers, Monopoly, Unfair Competition